Functional roles of the amino terminal domain in determining biophysical properties of Cx50 gap junction channels - Xin, Li; Bai, Donglin (Frontiers in Physiology, 2013)
Communication through gap junction channels is essential for synchronized and coordinated cellular activities. The gap junction channel pore size, its switch control for opening/closing, and the modulations by chemicals can be different depending on the connexin subtypes that compose the channel. Recent structural and functional studies provide compelling evidence that the amino terminal (NT) domains of several connexins line the pore of gap junction channels and play an important role in single channel conductance (γj) and transjunctional voltage-dependent gating (Vj-gating). This article reviews recent studies conducted on a series of mutations/chimeras in the NT domain of connexin50 (Cx50). Functional examination of the gap junction channels formed by these mutants/chimeras shows the net charge number at the NT domain to be an important factor in γj and in Vj-gating. Furthermore, with an increase in the net negative charge at the NT domain, we observed an increase in the γj, as well as changes in the parameters of the Boltzmann fit of the normalized steady-state conductance and Vj relationship. Our data are consistent with a structural model where the NT domain of Cx50 lines the gap junction pore and plays an important role in sensing Vj and in the subsequent conformational changes leading to gating, as well as in limiting the rate of ion permeation.